PLOT LAWS IN JOHNSON’S KNIVES OUT MOVIE - Putri, Ni Kadek Kenaka (LITERA : Jurnal Bahasa Dan Sastra, 2022)
ABSTRACTThe article aims to identify and analyze the plot laws in the 2019 box office movie Knives Out,written and directed by Rian Johnson. William Kenney's plot theory (1966a) was applied inthis study. The data source was taken from the movie Knives Out and it is applied qualitativeresearch methodologies including observation and documentation using a note-takingtechnique. The results of the analysis are six plot laws, namely plausibility, surprise, suspense,plot and unity, plot as unity, and plot as expression.Keywords: Plot, Plot Laws, LiteratureABSTRAKArtikel ini bertujuan untuk mengidentifikasi dan menganalisis hukum plot dalam film box officetahun 2019 berjudul Knives Out, yang disutradarai dan ditulis oleh Rian Johnson. Teori plotoleh William Kenney (1966a) diterapkan dalam penelitian ini. Sumber data diambil dari filmKnives Out dengan menggunakan metodologi penelitian kualitatif meliputi observasi dandokumentasi dengan teknik mencatat. Hasil yang ditemukan dalam analisis adalah enamhukum plot yaitu plausibility, surprise, suspense, plot and unity, plot as unity, dan plot asexpression.Kata Kunci: Plot, Hukum Plot, Literatur